PENGARUH SEGMENTASI PASAR TERHADAP KEPUTUSAN PEMBELIAN PRODUK TELKOM SPEEDY DI PT TELEKOMUNIKASI INDONESIA CABANG MALANG - Fullchis Nurtjahjani; Asminah Rachmi; Masreviastuti Masreviastuti (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This study takes the theme of some factor as determine for sales. In this study sampled 140 people as speedy costumer from PT. Telekomunikasi Indonesia. Quantitative study in which respondents were obtained from questionnaires distributed is used as the primary data are processed with SPSS. Respondent response assessed the range of 1 – 5, with the Likert scale strongly disagree to strongly agree.Based on the result of the research, from the description of the data respondent majority were male with ages between 36 to 40 years. Trials performed are validity and reliability is to test the validity of the questionnaire wer distributed, the t test for testing the correctness of the formulated hypotheses, correlation and regression test to examine the relationship and influence of each costumer relationship market segmentingvariables that aregeographics, demographics, psychographics and behaviour.Based on trials carried out that there is a truth of the hypothesis formulated, namely that there is a significant relationship and effect betweengeographics, demographics, psychographics and behaviourwith buying decision.